2018
DOI: 10.1155/2018/5896786
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Role of Exercise in Inhibiting mTOR Signaling in Triple‐Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) does not express estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 and is characterized by its aggressive nature, lack of targets for targeted therapies, and early peak of recurrence. Due to these specific characteristics, chemotherapy does not usually yield substantial improvements and new target therapies and alternative strategies are needed. The beneficial responses of TNBC survivors to regular exercise, including a reduction in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 169 publications
(192 reference statements)
1
20
0
Order By: Relevance
“…Many scientific reports indicate a protective effect of physical activity on breast cancer (8,9,13,(15)(16)(17), including in patients after comprehensive breast cancer treatment (8,9,(18)(19)(20)(21)(22)(23)(24). From the results of our study, we found two mechanisms which confirm these observations, namely desensitization of cells due to reduced expression of ER and PR, as well as increased apoptosis which positively correlated with the level of training intensity.…”
Section: Discussionsupporting
confidence: 85%
“…Many scientific reports indicate a protective effect of physical activity on breast cancer (8,9,13,(15)(16)(17), including in patients after comprehensive breast cancer treatment (8,9,(18)(19)(20)(21)(22)(23)(24). From the results of our study, we found two mechanisms which confirm these observations, namely desensitization of cells due to reduced expression of ER and PR, as well as increased apoptosis which positively correlated with the level of training intensity.…”
Section: Discussionsupporting
confidence: 85%
“…54,55 With some cancers, it is generally accepted that autophagy can suppress tumor initiation and cancer growth; and since autophagy blocks growth and increases breakdown of proteins, this is quite logical. 56,57 (Cuervo, 2004(Cuervo, , 2008. Cancer cells often have much lower levels of basal autophagy than normal cells.…”
Section: Role Of Autophagy and Hormesis In Disease And Agingmentioning
confidence: 99%
“…In certain cancers, mTORC1 inhibitors have demonstrated anticancer effects (Table 1). 56 Metformin, a drug widely used in type 2 diabetes, also activates autophagy but not directly through the mTORC1 system (Table 1). 72 This drug increases AMPK, a protein molecule that signals the energy status of the cell (Figure 2).…”
Section: Central Role Of Mtorc1 and Related Cell Signaling Pathwaysmentioning
confidence: 99%
“…Moreover, through PGC-1 α phosphorylation, aerobic exercise influences other transcription factors, like peroxisome proliferator-activated receptor- γ (PPAR γ ), as well as estrogen-related receptors, ERR α and ERR γ , which control mitochondrial energy metabolism via the tricarboxylic acid (TCA) cycle, FAO, and oxidative phosphorylation [ 149 , 150 ]. Endurance and, to a lesser extent, resistance exercises have been shown to activate AMPK, and inhibit mTOR in non-muscular tissues as well, such as liver and fat [ 151 ]. This leads us to surmise that this metabolic setting also works synergistically with the immune system, which has its proinflammatory phenotype aggravated in states of overfeeding and nutrient excess, triggering chronic low-grade inflammation, and in states of fasting and exercise, an anti-inflammatory state.…”
Section: Exercise As a Regulator Of Immunometabolismmentioning
confidence: 99%